Accuracy and precision of 3D-printed implant surgical guides with different implant systems: An in vitro study - Yeung, Matthew; Abdulmajeed, Aous; Carrico, Caroline K.; Deeb, George R.; Bencharit, Sompop (The Journal of prosthetic dentistry, 2020)
Implant guided surgery systems promise implant placement accuracy and precision beyond straightforward nonguided surgery. Recently introduced in-office stereolithography systems allow clinicians to produce implant surgical guides themselves. However, different implant designs and osteotomy preparation protocols may produce accuracy and precision differences among the different implant systems. The purpose of this in vitro study was to measure the accuracy and precision of 3 implant systems, Tapered Internal implant system (BioHorizons) (BH), NobelReplace Conical (Nobel Biocare) (NB), and Tapered Screw-Vent (Zimmer Biomet) (ZB) when in-office fabricated surgical guides were used. A cone beam computed tomography (CBCT) data set of an unidentified patient missing a maxillary right central incisor and intraoral scans of the same patient were used as a model. A software program (3Shape Implant Studio) was used to plan the implant treatment with the 3 implant systems. Three implant surgical guides were fabricated by using a 3D printer (Form 2), and 30 casts were printed. A total of 10 implants for each system were placed in the dental casts by using the manufacturer's recommended guided surgery protocols. After implant placement, postoperative CBCT images were made. The CBCT cast and implant images were superimposed onto the treatment-planning image. The implant positions, mesiodistal, labiopalatal, and vertical, as well as implant angulations were measured in the labiolingual and mesiodistal planes. The displacements from the planning in each dimension were recorded. ANOVA with the Tukey adjusted post hoc pairwise comparisons were used to examine the accuracy and precision of the 3 implant systems (α=.05). The overall implant displacements were −0.02 ±0.13 mm mesially (M), 0.07 ±0.14 mm distally (D), 0.43 ±0.57 mm labially (L), and 1.26 ±0.80 mm palatally (P); 1.20 ±3.01 mm vertically in the mesiodistal dimension (VMD); 0.69 ±2.03 mm vertically in the labiopalatal dimension (VLP); 1.69 ±1.02 degrees in mesiodistal angulation (AMD); and 1.56 ±0.92 degrees in labiopalatal angulation (ALP). Statistically significant differences (ANOVA) were found in M (P=.026), P (P=.001), VMD (P=.009), AMD (P=.001), and ALP (P=.001). ZB showed the most displacements in the M and vertical dimensions and the least displacements in the P angulation (P<.05), suggesting statistically significant differences among the M, VMD, VLP, AMD, and ALP. NB had the most M variation. ZB had the least P deviation. NB had the fewest vertical dimension variations but the most angulation variations. Dimensional and angulation displacements of guided implant systems by in-office 3D-printed fabrication were within clinically acceptable limits: <0.1 mm in M-D, 0.5 to 1 mm in L-P, and 1 to 2 degrees in angulation. However, the vertical displacement can be as much as 2 to 3 mm. Different implant guided surgery systems have strengths and weaknesses as revealed in the dimensional and angulation implant displacements.